Approaches for Working with the Body in the Design of Electronic Music Performance Systems. - Kirby, Jenn (Contemporary Music Review, 2023)
This article outlines a body-centred focus in the design of performance systems for electronic music. Through a movement-led design process, I discuss the interaction of the body, controllers, data and mapping. A flat hierarchy approach to performance system design aims to support bodily autonomy in performance, challenge human-machine dualism and expand the definition of virtuosity in performance to include system virtuosity. The affordances and behaviours of the components of performance systems are discussed in terms of their cooperation. With an awareness of the non-neutrality of data, controllers, and sensors, I outline methods for making adaptive and flexible systems which respond to and respect individual bodies. This embodied and hybrid approach to system design can facilitate posthuman expression in electronic music performance.